Modeling college student intimate partner violence perpetration, eating disorder symptomatology, and alcohol salience - Elizabeth A. Claydon; Rose Marie Ward; Danielle M. Davidov; Keith J. Zullig (Springer, 2024)
Abstract Intimate partner violence (IPV) perpetration's relationship with alcohol salience to college experience and eating disorder (ED) symptomatology is not well understood. Midwestern university students (n = 1580) participated in an online survey. Structural equation models examined the relationship between these variables. All models fit the data well, however, the risk factors of IPV perpetration or alcohol use were not significantly associated with ED symptomatology. However, IPV perpetration was significantly associated with both alcohol use (β = .13, p < .01) and alcohol salience (β = .11, p < .01). College students reported higher levels of perpetration and alcohol salience, which may indicate alcohol-fueled social interactions.